Opening the pandora’s box of issues in the Industrialised Building System (IBS) in Malaysia: a thematic review - Mohd Zairul (Tamkang University Press, 2021)
Under the Malaysian Construction Industry Transformation Programme (CITP) 2016–2020, IBS has been proposed as one of the alternative solutions for replacing conventional construction. Numerous IBS advantages have been documented and discovered since its first implementation in the 90s’. However, the literature still has inadequate studies that deliberate on IBS issues. Hence, this paper adopts a thematic review based on the issues captured in publications pertaining IBS from 2016 to 2021. The strategy of this article involved an investigation via an extensive review paper on IBS and analysis using thematic review. The findings from the code-to-document report in ATLAS.ti 8 revealed several issues in IBS based on the pattern highlighted in the literature. The outcomes are expected to benefit the direction of future research and to identify the gap for future solutions in IBS-related projects in Malaysia.